The U. S. Army order of battle: Mediterranean and - Madej, Victor (Allentown Game Publishing Company, 1984)
This book summarizes of all the major units that fought in the Mediterranean and European Theatre of operations in World War II. Here in one compact location are the details of Americas eastern front. The study starts with participant lists of 22 campaigns: from Egypt and Libya to Central Europe, followed by the dozen assault operations that were involved.
Keywords: Army